Independent Scientific Review under the Endangered Species Act. (13th February 2019) - Murphy, Dennis D; Weiland, Paul S
Abstract: The directive from Congress in the Endangered Species Act obliging the US Fish and Wildlife Service and National Marine Fisheries Service along with other federal agencies to use the best available scientific information in their determinations—and calls from stakeholder communities to show that they have done so—have led the federal wildlife agencies to seek external, expert review of their determinations with increasing frequency over time. In the present article, we survey the agency determinations that may be subject to independent science review and the technical tasks embedded in those determinations that can benefit from such review. We go on to identify common failures in scientific review that compromise the quality and reliability of agency determinations and then describe the attributes of independent scientific reviews that enable the agencies to discharge their statutory duties while seeking to conserve threatened and endangered species and the ecosystems on which they depend.